Evidence for an Altered Sex Ratio in Clinic‐Referred Adolescents with Gender Dysphoria. (1st March 2015) - Aitken, Madison; Steensma, Thomas D.; Blanchard, Ray; VanderLaan, Doug P.; Wood, Hayley; Fuentes, Amanda; Spegg, Cathy; Wasserman, Lori; Ames, Megan; Fitzsimmons, C. Lindsay; Leef, Jonathan H.; Lishak, Victoria; et al.
ABSTRACT: Introduction: The number of adolescents referred to specialized gender identity clinics for gender dysphoria appears to be increasing and there also appears to be a corresponding shift in the sex ratio, from one favoring natal males to one favoring natal females. Aim: We conducted two quantitative studies to ascertain whether there has been a recent inversion of the sex ratio of adolescents referred for gender dysphoria. Methods: The sex ratio of adolescents from two specialized gender identity clinics was examined as a function of two cohort periods (2006–2013 vs. prior years). Study 1 was conducted on patients from a clinic in Toronto, and Study 2 was conducted on patients from a clinic in Amsterdam. Results: Across both clinics, the total sample size was 748. In both clinics, there was a significant change in the sex ratio of referred adolescents between the two cohort periods: between 2006 and 2013, the sex ratio favored natal females, but in the prior years, the sex ratio favored natal males. In Study 1 from Toronto, there was no corresponding change in the sex ratio of 6, 592 adolescents referred for other clinical problems. Conclusions: Sociological and sociocultural explanations are offered to account for this recent inversion in the sex ratio of adolescents with gender dysphoria.